Pengaruh Good Corporate Governance Terhadap Integritas Laporan Keuangan - Ririn Sari Dewi; Yayah Syahriyah (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the effect of Good Corporate Governance (GCG) mechanisms, namely managerial ownership, institutional ownership, audit committee, and independent commissioners on the integrity of financial statements. Financial statement integrity is proxied by earnings quality measured using the ratio of operating cash flow to net income. This study uses a quantitative approach with secondary data obtained from financial statements of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2020–2024. The sampling technique used purposive sampling, resulting in 11 companies with 55 observations. Data analysis was carried out using panel data regression. The results show that simultaneously GCG variables have a significant effect on financial statement integrity. Partially, managerial ownership has a significant effect, while institutional ownership, audit committee, and independent commissioners have no significant effect